Comparing Alkaline Phosphatase PhoX-Encoding Genes in Two Contrasting Habitats of the Large Eutrophic Lake Taihu, China. Issue 6 (3rd July 2018) - Dai, Jiangyu; Gao, Guang; Wu, Shiqiang; Wu, Xiufeng; Tang, Xiangming; Shao, Keqiang; Xue, Wanyun; Yang, Qianqian; Chen, Dan
ABSTRACT: River mouth areas of eutrophic lakes have frequent cyanobacterial blooms and high organophosphate mineralization rates. To determine the genetic background of the high organophosphate mineralization rate in river mouth areas of eutrophic lakes, we compared the diversity and abundance of bacterial alkaline phosphatase PhoX-encoding genes in the river mouth areas and the lake center within the large eutrophic Lake Taihu, China. Results showed that the seasonal average values of phosphorus content, bacterial alkaline phosphatase activity, diversity, and abundance of bacterial phoX in the river mouths were significantly higher than those in the lake center, and 47% of all identified genotypes were present only in the river mouths. The genotypes most similar to alphaproteobacterial phoX dominated in both regions, with 72% and 64% of the total genotypes in the lake center and river mouths, respectively. More than 40% of the total phoX genotypes were only found in the river mouths, however, indicating the special microbial nature in this hypereutrophic habitat. The differences in contents of dissolved organic carbon and phosphorus were related to the divergences of bacterial phoX genotypes in these two contrasting habitats. Because some dominant genotypes most similar to phoX genes of alphaproteobacterial genus were observed only in the river mouth areas, such as Microvirga sp. WSM3557, and because the hydraulic retention time of Lake Taihu is insufficient to shape the special bacterial groups in the river mouths, allochthonous inputs of nutrients and bacterial species could make contributions to explain the different organophosphate mineralization rates in these two contrasting habitats of the large eutrophic lake.